2013
DOI: 10.4314/ahs.v13i3.20
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic bacteriuria in diabetes mellitus patients in Southwest Cameroon

Abstract: Background: Asymptomatic bacteriuria (ASB) is common in diabetics and predisposes these patients to more severe urinary tract infections (UTIs). Reports on the prevalence and etiology of ASB especially in developing countries appear contradictory. Objectives: To determine the prevalence and etiology of ASB and antimicrobial resistance of urinary isolates in diabetics and non-diabetics. Methods: The study involved a total of 265 participants including 154 diabetes mellitus patients and 111 non-diabetics in Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
7
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 18 publications
8
68
7
3
Order By: Relevance
“…However, it was lower than study findings reported from Italy (54.1%) versus (58.2%) [16] and Nepal (41.7%) versus (40) in the above order. In addition, the isolation rates of K. pneumoniae in the present study were 14.3% versus 11.1% which was similar to those reported from Cameroon (15.9%) [14] and Libya (13% versus 14%) [13]. …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, it was lower than study findings reported from Italy (54.1%) versus (58.2%) [16] and Nepal (41.7%) versus (40) in the above order. In addition, the isolation rates of K. pneumoniae in the present study were 14.3% versus 11.1% which was similar to those reported from Cameroon (15.9%) [14] and Libya (13% versus 14%) [13]. …”
Section: Discussionsupporting
confidence: 89%
“…However, it is lower than a report from Cameroon (36.3%) [14]. This could be due to the appropriate use of antibiotics that may reduce the proliferation of S. saprophyticus bacteria or good personal hygiene practice.…”
Section: Discussionmentioning
confidence: 61%
“…Gingivitis is a consistent feature found in children with poorly controlled type 1 diabetes mellitus, and the level of glycemic control may be more important in determining the severity of gingival inflammation than the quality of plaque control . In adults with diabetes mellitus it is much more difficult to detect the effects of this endocrine disease on gingival diseases, and only limited evidence is available since most studies have evaluated gingival inflammation in association with attachment loss …”
Section: Plaque‐induced Gingivitis Exacerbated By Systemic Conditionsmentioning
confidence: 99%
“…7 Oral pathology is one of the major complications in DM2 patients and, therefore, it is important to intervene early in order to reduce the risk of a future interaction between these pathologies. [8][9][10][11] The emphasis on similarities between determinants of OH and GH is broadly consistent and leads to the conclusion that OH is an integral part of GH. 12 Some studies have identified associations between oral pathology and DM2, 1,8,13,14 and both are associated with a worse perceived GH 15 and worse oralhealth quality of life due to OH manifestations.…”
Section: Introductionmentioning
confidence: 88%